2017
DOI: 10.1159/000477867
|View full text |Cite
|
Sign up to set email alerts
|

Serum Irisin Predicts Mortality Risk in Acute Heart Failure Patients

Abstract: Background/Aims: Irisin is a peptide hormone cleaved from a plasma membrane protein fibronectin type III domain containing protein 5 (FNDC5). Emerging studies have indicated association between serum irisin and many major chronic diseases including cardiovascular diseases. However, the role of serum irisin as a predictor for mortality risk in acute heart failure (AHF) patients is not clear. Methods: AHF patients were enrolled and serum was collected at the admission and all patients were followed up for 1 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 29 publications
2
36
0
Order By: Relevance
“…Previous studies have demonstrated that irisin stimulation increased the metabolic rate, mitochondrial content [6,32], and FFA oxidation in myocytes [3,7]. Moreover, a positive correlation of mortality risk in acute heart failure and serum irisin was also observed, suggesting irisin can be used as a predictive biomarker for cardiovascular diseases [33]. In this study, we demonstrated that exercise may enhance cAMP to stimulate muscular Pgc-1α expression, which interacts with the transcription factor CREB to induce Fndc5 expression.…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies have demonstrated that irisin stimulation increased the metabolic rate, mitochondrial content [6,32], and FFA oxidation in myocytes [3,7]. Moreover, a positive correlation of mortality risk in acute heart failure and serum irisin was also observed, suggesting irisin can be used as a predictive biomarker for cardiovascular diseases [33]. In this study, we demonstrated that exercise may enhance cAMP to stimulate muscular Pgc-1α expression, which interacts with the transcription factor CREB to induce Fndc5 expression.…”
Section: Discussionsupporting
confidence: 60%
“…Differences in study design, methodologies used to assess irisin, and included patients make comparison between the present study and previous studies difficult. It should be noted that previous studies [13,[19][20][21] were often with small samples (less than 200) and at single sites, while the present study was a multicenter study with a large sample size (N = 1530).…”
Section: Discussionmentioning
confidence: 91%
“…However, another study reported that low serum irisin level was an independent predictor of coronary artery severity in patients with stable coronary artery disease [20]. Conversely, Shen et al [21] identified high serum irisin as a predictive biomarker for 1-year all-cause mortality in acute heart failure patients. In our study, the results showed that the reduced serum concentration of irisin was a useful prognostic marker of functional outcome and mortality in Chinese patients with stroke independent of established conventional risk factors.…”
Section: Discussionmentioning
confidence: 98%
“…Of particular interest in this context is irisin, a newly identified adipomyokine derived from fibronectin type III domain containing 5 (FNDC5), which has gained attention for its potential in the prevention and treatment of obesity and T2DM [6,7]. In this regard, the circulating levels of irisin were found to be altered in obese individuals and diabetic patients [8]; these levels were considered to be one biomarker for the prediction of the development of diabetes and mortality risk of cardiovascular diseases [9,10]. We and others have demonstrated that, in an overnutrition state, irisin can restore metabolic homeostasis, thereby alleviating insulin resistance and protecting cell function as well as survival in hepatic tissues [11][12][13].…”
Section: Introductionmentioning
confidence: 99%